Diagnosis of cutaneous tuberculosis (lymph node scrofuloderma) using the Xpert MTB/RIF® method, - Costa,Lilian Lemos (2021)
Abstract Cutaneous tuberculosis is a rare infection that is difficult to diagnose, because it shows less sensitivity and specificity in classic complementary exams when compared with the pulmonary form. The Xpert MTB/RIF® method offers an early diagnosis that identifies the DNA of Mycobacterium tuberculosis and the main mutations that give the bacterium resistance to rifampicin. The authors present a case of scrofuloderma whose diagnosis was quickly obtained through the secretion of a cervical lesion, allowing an early diagnosis and the initiation of appropriate treatment.